2016
DOI: 10.1089/tmj.2015.0095
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Patient Recruitment, Implementation, and Fidelity in a Mobile Telehealth Study

Abstract: The current article presents data on the influence of contextual factors on the conduct of this MTH study and underlines the need for these processes to be assessed and reported adequately in future MTH research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 46 publications
(39 reference statements)
0
24
0
8
Order By: Relevance
“…Figure 2 illustrates the growing research interest in context within the field of implementation science, however, a slight decline is noted within the previous 2 years. Thirty-four of the included studies used a qualitative approach [8,19,26 [20,25,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87], while 12 conducted a mixed methods evaluation [27,28,34,42,46,48,51,53,55,58,65,70]. Studies using a qualitative approach commonly used interview methods, while quantitative studies predominantly employed surveys for data collection.…”
Section: Provides a Meaningful Definition Of An Element Of Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 illustrates the growing research interest in context within the field of implementation science, however, a slight decline is noted within the previous 2 years. Thirty-four of the included studies used a qualitative approach [8,19,26 [20,25,[72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87], while 12 conducted a mixed methods evaluation [27,28,34,42,46,48,51,53,55,58,65,70]. Studies using a qualitative approach commonly used interview methods, while quantitative studies predominantly employed surveys for data collection.…”
Section: Provides a Meaningful Definition Of An Element Of Contextmentioning
confidence: 99%
“…Within many of these definitions, the influence of context on implementation success is acknowledged as critical [19, 27, 35, 38-40, 55, 68, 70, 71]. Some papers elaborate that contextual factors are the barriers and facilitators encountered during implementation [39,40,70,71]. Within the included papers context related to the pre-existing structural and organisational factors of the setting [27], or also included dynamic determinants that arose as implementation progressed [70].…”
Section: Provides a Meaningful Definition Of General Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of clinical nurses' and other clinical and research members' perceptions of recruiting to clinical research have identified facilitators of effective recruitment, including strong communication between research study teams, lead nurses and other healthcare staff (Baron, Hirani, & Newman, 2016;Nurmi, Pietil€ a, Kangasniemi, & Halkoaho, 2015;Peters-Lawrence et al, 2012;Reynolds et al, 2013); integrated clinical and academic teams on site and doctors mentioning the study within routine consultation (Newington & Metcalfe, 2014); and clinical teams holding positive attitudes towards research (Borschmann, Patterson, Poovendran, Wilson, & Weaver, 2014;French & Stavropoulou, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…También se les consulto cuales son las principales actividades que realizan a través de sus dispositivos móviles, sigue liderando la mensajería instantánea con el 42% enviar y recibir mensaje, otro uso interesante del cual el docente es testigo ya que en las aulas de clases se evidencia la ausencia de cuadernos ya que con una foto se resuelve todo, el 20% lo usa como cuaderno virtual, medio de apuntes, igualmente el 20% en búsqueda de información y un 18% para compartir archivos tabla 1. De acuerdo a un estudio hecho, Baron (2016) se encontró que los estudiantes que usan aplicaciones móviles suelen recordar con mayor facilidad el patrón de búsqueda (habilidad procedural), que el resultado por sí mismo (habilidad cognitiva), es decir, el cerebro se adapta al uso de la tecnología, lo cual puede ser beneficioso en el trabajo bajo presión. Para el 78% de los docentes encuestados, el M-learning fomenta el aprendizaje colaborativo entre los estudiantes, y su uso ha logrado mejorar el rendimiento académico de los estudiantes en un 90% , debido que al poder usarlo como soporte en el proceso de enseñanza aprendizaje, los estudiantes pudieron enviar sus tareas a tiempo por ese medio así como también pudieron ser partícipes en los talleres de modo virtual a través del uso de video llamada por medio de la aplicación de WhatsApp instalada en la mayoría de los smartphones de los estudiantes.…”
Section: Resultsunclassified